Combined Karapandzic–Abbé/Estlander/Stein flap for subtotal and total lower lip reconstruction. Issue 3 (March 2019) - Uglesic, Vedran; Amin, Kavit; Dediol, Emil; Kosutic, Damir
Summary: Background: Lower lip reconstruction remains a challenging task due to multi-functional and high aesthetic requirements that have to be achieved for successful outcome. This is particularly true to near-total lower lip defects, encompassing over 70% of lower lip loss due to cancer, trauma or burns. Despite the fact that numerous flaps and their modifications have been described over the past century, only a few valuable techniques and concepts withstood the test of time for sub-total lower lip defects, each having their own drawbacks. We describe a new approach to these defects combining bilateral Karapandzic and Abbe/Estlander/Stein flaps, not reported so far, and present our long term outcomes. Methods: From 2012 to 2016, five patients with T4 lower lip squamous cell carcinoma (SCC) underwent near-total and total lower lip resection and reconstruction with a combination of bilateral Karapandzic flap and double Abbé/Estlander/Stein flaps from the upper lip. Results: Our patients were between 44 and 88 years old (mean 66.6). All flaps healed uneventfully in all patients. Patients were followed up between 18 and 60 months (mean follow up 33.6 months). There were no local tumor recurrencies. All patients were able to eat perorally whilst reconstructed lips were fully functional. No drooling was observed and aesthetic outcomes were excellent. Conclusions: Combined bilateral Karapandzic and Abbe/Estlander/Stein flaps can produce excellent functional and aesthetic outcomes in near total and total lower lip reconstructions and should be considered a reliable reconstructive option in patients with more then 70% of lower lip loss.